Micromechanical Modeling of Unreinforced Masonry Arches Accounting for Flexural Hinges and Shear Slidings. Issue 10 (3rd October 2022) - Nocera, Mariacarla; Gatta, Cristina; Addessi, Daniela; Liberatore, Domenico
ABSTRACT: This paper investigates the structural response of unreinforced masonry arches subjected to asymmetrical vertical concentrated loads, by studying global force-displacement response curves and collapse mechanisms. The micromechanical modeling approach is adopted, which describes the detailed arrangement, geometry and mechanical properties of the masonry constituents. This is introduced in a 2D finite element procedure modified and enriched to describe masonry curved geometry and the occurring damage and friction mechanisms. Linear elastic behavior is assumed for bricks, whereas a damage-friction law is considered for the mortar to describe flexural and shear failure mechanisms. First, to prove the efficiency of the adopted model, the response of experimentally tested arches is numerically reproduced. Then, a parametric analysis is performed to analyze the effect of the geometric parameters on the global structural response. It is proved that, as the thickness/internal radius ratio increases, the failure mechanism moves from the formation of flexural hinges to shear sliding, leading to a more brittle response. Moreover, influence of relevant material parameters is investigated and the numerical outcomes are compared with those obtained by the classical limit analysis approach. It appears that the maximum predicted load generally exceeds the limit analysis collapse value, depending on the material properties mostly influencing the failure mechanisms.